CAN KIDS LEARN BY THEMSELVES USING TECHNOLOGY AND WHAT DO THEY LEARN? - Shabnam Husnoo; Goonesh K Bahadur; Mohammad Santally (European Scientific Journal, ESJ, 2014)
This study presents the method and results of an experiment conducted to investigate whether kids (5-8 years) can use technology to learn in such unsupervised learning conditions. This study also assesses the skills and understanding that children develop through unsupervised technology exposure. The study, carried over 6 months, focused on two primary schools (School ‘A’ and School ‘B’) both found in Mauritius. Both quantitative and qualitative approaches were adopted to collect data for this investigation. The qualitative data focused on interviews with kids, examination of the students’ work on PCs, observation in their ability to explore an interface, use a mouse, keyboard and the Internet. The quantitative data provide information which is easy to analyze statistically and fairly reliable. Descriptive statistics and charts have been used to analyze the quantitative data. It has been found that kids who had access to computers and Internet-based resources both at school and at home can self – educate themselves, but only to some extent because there will come such a moment when they will need a facilitator for guidance